Yield reductions in grain maize associated with the presence of European corn borer and Gibberella stalk rot in Québec - Hudon, M.; Bourgeois, G.; Boivin, G.; Chez, D. (Phytoprotection, 1992)
The impact of European corn borer (Ostrinia nubilalis) [Lepidoptera: Pyralidae] infestation and stalk rot infection caused by Gibberella zeae on yield of eight grain maize (Zea mays) inbreds, two commercial and six experimental hybrids was evaluated from 1975 to 1980. Three criteria were used: leaf feeding, total plant damage at harvest and tunnel length/plant height ratio. For most criteria, the cultivars were significantly different and the artificial European corn borer infestation had an effect almost every year. Although G. zeae can have a signifiant effect on plant damage at harvest and yield of grain maize, no consistent link was found between stalk rot and European corn borer.